The complete mitochondrial genome of sponge Tethya sp. (Demospongiae, Tethyida, Tethyidae). Issue 1 (1st January 2016) - Zhang, Yuan; Huang, Dan; Wang, Dexiang; Ding, Shaoxiong
Abstract: The complete mitochondrial genome of Tethya sp. was studied. This is the second complete mitochondrial report on the family Tethyidae. The mitochondrial genome of Tethya sp. is 20, 582 bp in length, containing 14 protein-coding genes and 25 tRNA genes, with 2 rRNA genes. Our phylogenetic result suggested that Tethya sp. converged well with Tethya actinia, which further verified the morphological result. We anticipate our study to shed light on future molecular studies of demosponges.